Upper eyelid swelling as the first symptom of frontal sinus mucocele in a 9-year-old girl – case report - Rakusiewicz, Klaudia; Czeszyk, Agnieszka; Kanigowska, Krystyna; Hautz, Wojciech (Klinika Oczna / Acta Ophthalmologica Polonica, 2023)
The aim of the study is to present a case of a 9-year-old girl with mucocele of the frontal sinus penetrating into the anterior fossa of the skull and infiltrating the upper wall of the orbit and manifesting with upper eyelid swelling. On the basis of the clinical findings and additional imaging tests, the girl was diagnosed with mucocele of the frontal sinus.